(3GdJHUQI aj GdbQGAGJ GdYTQIs - (3nepqcj Hf CHj WGdH nMoqehT Hf eMeO Hf eNJGQ GdCfOdSj GdbjSj, CHh eMeO,J (B437 (3g` s ((3eMeO Hf GHQGgje Hf UGdM GdMfai s)
(3ChdgG (B:s
(3bGd GHh eMeO eci Hf CHj WGdH hbO QZH Edi QGZHhf ai LejY cJGH ai GUhd GdbQGAGJ hPcQ eG GNJda ajg GdeTghQhf ef GdbQGA aNQLJ ai gPG GdcJGH GQHY YTQI QhGjI Yf GdSHYI GdeTghQjf s
(3BNQgG (B:s
(3hEfeG YedJ gPG GdcJGH OQLkG ddeHJOF hdef GQGO GdMaX QMe Gddg YHOkG EfJaY Hg hbQC ajg hCNdU Pdc ddg hJcda GdHMK Ydjg hGdfXQ ajg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B286 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B3s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs